Comment on the intravenous tranexamic acid use in revision total joint arthroplasty - He J; Liu Y (Dove Medical Press, 2018)
Jieyu He, Youshuo Liu Department of Geriatrics, Second Xiangya Hospital, Central South University, Changsha 410011, China Kuo et al thoroughly evaluated the safety and efficacy of intravenous tranexamic acid in revision total joint arthroplasty (TJA) via aspects of blood loss and transfusion, events of venous thromboembolism.1 We consider application of this drug of great value in revision TJA. However, we would like to address several concerns related to this meta-analysis.  Author's reply  Feng-Chih Kuo,1 Pao-Yen Lin,2 Jun-Wen Wang,1 Po-Chun Lin,1 Mel S Lee,1 Antonia F Chen3 1Department of Orthopaedic Surgery, Kaohsiung Chang Gung Memorial Hospital, College of Medicine, Chang Gung University, Kaohsiung, Taiwan; 2Department of Psychiatry, Kaohsiung Chang Gung Memorial Hospital, College of Medicine, Chang Gung University, Kaohsiung, Taiwan; 3Department of Orthopaedic Surgery, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USA  We read the letter from He and Liu in response to our recently published article entitled “Intravenous tranexamic acid use in revision total joint arthroplasty: a meta-analysis”1 with interest.  View the original paper by Kuo and colleagues.